The Determinant Factors in Managing Dengue Hemorrhagic Fever During the Covid-19 Pandemic: A Literature Review - vitria wuri handayani; Alfa Nur Husna; H. Amandus; Revani Hardika; Maulidyah Salim; Mathe (Jurnal Ilmiah Kesehatan, 2022)
During the COVID-19 Pandemic, differentiating tropical infectious diseases and COVID-19 can be challenging due to overlapping clinical presentations. Fever and nonspecific symptoms in early COVID-19 may be challenging to distinguish from dengue hemorrhagic fever (DHF) and malaria because respiratory signs may be absent or manifest later in the disease course. This literature review analyzes the determinant factors in managing DHF during the COVID-19 Pandemic. This paper was a systematic literature review of national and international journals in the Google Scholar and PubMed databases from 2019 to 2022. We used the PICOS framework to find articles. The Indonesian and English keywords were the speed of health service, dengue hemorrhagic fever, and COVID-19. There were two included studies in this systematic review. The results showed that during the Covid-19 Pandemic and the dengue epidemic, a triage strategy was crucial to detect Covid-19 that could potentially be misdiagnosed as DHF. In addition, the first delay in seeking care treatment for dengue infection was due to financial constraints and previous dengue infection. Moreover, the second delay was because of the availability of transportation, traffic density, and residency location. Furthermore, the third delay was because of the hospital's capacity. Thus, the determinant factors of managing Dengue Hemorrhagic Fever during the COVID-19 Pandemic were the similarity of the signs and symptoms of dengue fever with Covid-19, financial aspects, transportation factors, the hospital distance, and hospital capacity.